1993
DOI: 10.1002/nme.1620360504
|View full text |Cite
|
Sign up to set email alerts
|

Trefftz method for Kirchhoff plate bending problems

Abstract: Kirchhoff plate bending problems were studied by both the Treffti direct and indirect approximations in which non-singular, complete TrefftL functions are used as the weighting and/or trial functions. The TrefftL direct method iiivolved only the quantities of engineering interest. Numerical results are given to show the efficiency and the excellent accuracy of the present method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Given the fact that RBF and Tre tz share some features the reproduction of the results obtained by Jin et al [33] was deemed relevant. Amongst those common features are, for example, that both techniques lead to global approximations of the relevant variables in a way which is more closely related than with, generally speaking, ÿnite element methods and that the number of unknowns=equations is usually much lower than that of standard ÿnite element techniques for obtaining similar accuracy.…”
Section: Numerical Testsmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the fact that RBF and Tre tz share some features the reproduction of the results obtained by Jin et al [33] was deemed relevant. Amongst those common features are, for example, that both techniques lead to global approximations of the relevant variables in a way which is more closely related than with, generally speaking, ÿnite element methods and that the number of unknowns=equations is usually much lower than that of standard ÿnite element techniques for obtaining similar accuracy.…”
Section: Numerical Testsmentioning
confidence: 96%
“…The methodology chosen for presenting the results and also the tests conducted follow closely that of Jin et al [33], a reference work for Tre tz formulation (which may also be considered, up to a certain point, meshless). Given the fact that RBF and Tre tz share some features the reproduction of the results obtained by Jin et al [33] was deemed relevant.…”
Section: Numerical Testsmentioning
confidence: 99%
“…Another regular boundary type approach is the Tre tz method, which has been widely used to deal with many types of problems, such as plane elasticity problems [14], plate bending problems [15] and acoustics [16], and the ÿrst applications of various modern forms of this method can be traced back to 1978 [17]. The boundary type Tre tz method basically employs the complete set of solutions satisfying the governing equation as the beginning step.…”
Section: Introductionmentioning
confidence: 99%
“…These unknowns are then obtained from the approximate satisfaction of the boundary conditions by means of collocation or in a weighted residual sense. Trefftz-based formulations have been studied by several authors, such as Jirousek and co-workers (of which Jirousek and Wrobleski [5] give a thorough account), Cheung et al [6], Jin et al [7], Zielinski and Zienkiewicz [8], Zielinski and Herrera [9], and Freitas and Ji [10] amongst others. Reviews on the subject may be found in Zielinski [11], Kita and Kamiya [12] and Jirousek and Wrobleski [5].…”
Section: Introductionmentioning
confidence: 99%